2010
DOI: 10.1063/1.3479905
|View full text |Cite
|
Sign up to set email alerts
|

Self-diffusion of poly(propylene glycol) in nanoporous glasses studied by pulsed field gradient NMR: A study of molecular dynamics and surface interactions

Abstract: Pulsed field gradient NMR is applied to investigate the self-diffusion of poly(proypylene glycol) in nanoporous glasses (nominal pore sizes of 2.5-7.5 nm). In general, the diffusion is slowed down by the confinement compared to the bulk. For native pore surfaces covered by hydroxyl groups the spin echo attenuation Ψ displays a bimodal behavior versus q(2)t (q-norm of a generalized scattering vector). This was explained assuming spatial regions of different diffusivities in a two-phase model. The slow component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…The fact that at the end of the process the segmental relaxation times are identical to the bulk might lead to the erroneous conclusion that there is little or even no effect of confinement on the polymer dynamics at the segmental level. Such a conclusion would not be in line with several experiments that have shown a speed-up of dynamics under confinement ,, or even a bimodal glass temperature. , Here this result is not unexpected as the imbibition temperature is located far above (typically 30–50 K) the glass temperature. On the other hand, imbibition at temperatures in the vicinity of T g is extremely slow.…”
Section: Results and Discussionmentioning
confidence: 56%
“…The fact that at the end of the process the segmental relaxation times are identical to the bulk might lead to the erroneous conclusion that there is little or even no effect of confinement on the polymer dynamics at the segmental level. Such a conclusion would not be in line with several experiments that have shown a speed-up of dynamics under confinement ,, or even a bimodal glass temperature. , Here this result is not unexpected as the imbibition temperature is located far above (typically 30–50 K) the glass temperature. On the other hand, imbibition at temperatures in the vicinity of T g is extremely slow.…”
Section: Results and Discussionmentioning
confidence: 56%
“…Recently, Kipnusu et al have shown that the dynamics of the chain mode is almost bulk-like at a high temperature region. Interestingly, this process becomes much faster at this regime only in the case of pores of the smallest diameter ( d = 4 nm) of sizes comparable to the radius of gyration of PPG (∼3.3 nm). Nevertheless, further lowering of temperature leads to the enhanced dynamics of the normal mode with respect to the bulk sample.…”
Section: Results and Discussionmentioning
confidence: 97%
“…The partitioning of the pore confined liquid in a slow component and in one with a dynamics close to the bulk liquid is representative for many other pore condensates and porous media, e.g., polymers [338] or other small molecules [319,339,340,341,342,343] in silica or silicon matrixes. The thermodynamic partitioning of pore-condensates in a film-condensed regime, strongly interacting with the pore walls, and in the capillary condensate in the pore centre, with a thermodynamics close to the bulk system, nicely documented in the discussion on capillary condensation, results obviously in an analogous partitioning of the molecular mobility -see the illustration in Fig.…”
Section: Self-diffusion Dynamicsmentioning
confidence: 99%